2007
DOI: 10.1038/sj.onc.1210555
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone enhances branching morphogenesis in the mouse mammary gland by increased expression of Msx2

Abstract: Branching morphogenesis within the peripubertal mouse mammary gland is directed by progesterone (P). A role for the homeobox-containing transcription factor, Msx2, during branching morphogenesis is suggested from its ontogenic expression profile and hormonal regulation. Herein, we define the spatio-temporal control of Msx2 expression, the regulation of its expression by P and its direct role in ductal branching morphogenesis. P induces Msx2 in the presence of estrogen (E) both in vitro and in vivo while absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
4

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 37 publications
(41 reference statements)
6
35
4
Order By: Relevance
“…EpH4 cells were originally derived from the mid-pregnant murine mammary gland (Pinkas and Leder, 2002;Reichmann et al, 1992) and lack PR (Satoh et al, 2007). Transfection of the EpH4 cells with cDNA for the mouse PR resulted in expression of PR-A (Satoh et al, 2007), which is known to act in an unliganded manner (Jacobsen et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…EpH4 cells were originally derived from the mid-pregnant murine mammary gland (Pinkas and Leder, 2002;Reichmann et al, 1992) and lack PR (Satoh et al, 2007). Transfection of the EpH4 cells with cDNA for the mouse PR resulted in expression of PR-A (Satoh et al, 2007), which is known to act in an unliganded manner (Jacobsen et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…In the mouse, mammary ductal elongation occurs through the action of E while lateral branching occurs through the interaction of E plus P. Tertiary ductal branching and alveolar development result from signaling pathways downstream of the PR and PrlR. We found that transfection of PR into EpH4 mouse mammary epithelial cells increased branching morphogenesis in collagen gels through induction of the homeobox gene Msx2 (Satoh et al, 2007). Additionally, the cooperative effects of these three hormones may occur in part due to mutual induction of each other's receptors.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…A growing body of evidence indicates a connection between dysregulated homeobox genes with disease and congenital abnormalities [21]. Expression of several homeobox genes, for example MSX-2, has been identified during the development of the mammary gland [22,23] where they are candidates for the orchestration of the cell signaling that enables the gland to undergo repeated cycles of growth and functional differentiation [24]. Homeobox genes are also known to be upregulated in tumors, where they have been linked to differentiation and prognosis [24][25][26][27].…”
mentioning
confidence: 99%